2011
DOI: 10.1021/ie200446y
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogenolysis of Glycerol to 1,2-Propanediol over Nano-Fibrous Ag-OMS-2 Catalysts

Abstract: Increasing demand for biodiesel production would lead to tremendous supply of glycerol as a coproduct, which is almost 10% by weight. Therefore, utilization of bioglycerol into valuable chemicals is timely to reduce the cost of biodiesel. Both 1,2and 1,3-propanediols are very useful chemicals which can be produced from glycerol. This paper describes a novel process for selective hydrogenolysis of glycerol to 1,2-propanediol over silver incorporated octahedral molecular sieve (OMS-2) catalyst. Also, the current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(33 citation statements)
references
References 28 publications
3
30
0
Order By: Relevance
“…Arrhenius plot was made by plotting ln (k/ L mol −1 h −1 ) vs. (1/T) (figure 10b). The calculated activation energy of glycerol hydrogenolysis over Cu/MgO catalyst in temperature range of 190-225 • C is found to be 28.7 ± 0.8 kcal/mol, a value in agreement with that reported by Sharma et al 19 (31.5 kcal/mol) and Yadav et al 33 (27.5 kcal/mol). This activation energy value also indicates that the hydrogenolysis reaction is intrinsically kinetically controlled.…”
Section: 2csupporting
confidence: 90%
See 1 more Smart Citation
“…Arrhenius plot was made by plotting ln (k/ L mol −1 h −1 ) vs. (1/T) (figure 10b). The calculated activation energy of glycerol hydrogenolysis over Cu/MgO catalyst in temperature range of 190-225 • C is found to be 28.7 ± 0.8 kcal/mol, a value in agreement with that reported by Sharma et al 19 (31.5 kcal/mol) and Yadav et al 33 (27.5 kcal/mol). This activation energy value also indicates that the hydrogenolysis reaction is intrinsically kinetically controlled.…”
Section: 2csupporting
confidence: 90%
“…This activation energy value also indicates that the hydrogenolysis reaction is intrinsically kinetically controlled. 33 From the current study it is observed that the MgO supported Cu catalysts increase the activity for hydrogenolysis of glycerol to produce 1,2-PDO in good yield. The increase in activity is due to the combined effects of metal dispersion over support and acidic strength which is confirmed by characterization results.…”
Section: 2cmentioning
confidence: 53%
“…Among various utilization routes of glycerol, the selective hydrogenolysis of glycerol to 1,2-propanediol (1,2-PDO) is of paramount research interest to the scientific community. The 1,2-PDO is a vital desirable chemical that can be used in a wide variety of industrial applications, such as pharmaceuticals, antifreeze additives, cosmetics, polymers, tobacco industries, etc [17][18][19]. 1,2-PDO is usually produced by a petrochemical approach through the hydration of hazardous propylene oxide, which is an expensive and environmentally unfriendly method [7].…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogenolysis of glycerol into 1,2-PDO, which is a valuable chemical mainly used for producing polymers, has been intensively reported over various metal catalysts such as Cu [18][19][20][21][22][23][24][25][26], Rh [27,28], Ru [29,30], Ni [31,32], Pt [33,34], and Ag [26,35]. In this reaction, HA is primarily generated in the dehydration of glycerol, and then hydrogenated into 1,2-PDO [15,16].…”
Section: Introductionmentioning
confidence: 99%